2022
DOI: 10.3390/ma15030807
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Water Balance Evaluation in Glass Ionomer Restorative Materials

Abstract: The complex role of water in glass ionomer cement (polyalkenoate) dental restorative materials has been studied, but much of the present understanding concerning water balance within these materials is based on very early studies and short-term experiments. This study evaluated the nature of the water species of six conventional and four resin modified glass ionomer restorative materials over 3 years using thermogravimetric analysis techniques. Materials were prepared, placed in crucibles, and stored in physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In vitro studies have shown that glass ionomer cements absorb more water than compo-sites [40]. Resin-modified glass ionomer cements showed higher water absorption than conventional glass ionomer cements due to the hydrophilicity of 2-hydroxyethyl methacrylate (HEMA) [CH₂=C(CH₃)COOCH₂CH₂OH] [41][42][43][44][45][46]. Fillers made of glass ionomers need to be covered with a protective varnish, as indicated by each manufacturer to prevent water absorption in the obturation and subsequently its degradation in the first hours after curing [47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that glass ionomer cements absorb more water than compo-sites [40]. Resin-modified glass ionomer cements showed higher water absorption than conventional glass ionomer cements due to the hydrophilicity of 2-hydroxyethyl methacrylate (HEMA) [CH₂=C(CH₃)COOCH₂CH₂OH] [41][42][43][44][45][46]. Fillers made of glass ionomers need to be covered with a protective varnish, as indicated by each manufacturer to prevent water absorption in the obturation and subsequently its degradation in the first hours after curing [47][48][49][50][51][52].…”
Section: Resultsmentioning
confidence: 99%
“…In the polyacid-salt matrix of the GIC kit, water exists in two forms: free water particles, which can be removed from the matrix by drying, and bound water particles, which are chemically locked in the matrix 80 . Since water plays an important role during cement maturation and ion diffusion 4 , properties of GICs are susceptible to both water uptake, as well as dehydration 81 , 82 .…”
Section: Discussionmentioning
confidence: 99%
“…For some GICs, with aging, the porosity of the material changes 83 , and the volume fraction of the bound water 83 . However, it was presented that GICs tend to increase the content of unbound water in time 80 . While we observed a great contrast in mechanical and tribological performance between the three tested GICs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Light activation of conventional glass ionomer cements (GICs) permits the formation of supplemental cross-links [34]. The disadvantages include great polymerization contraction and cytotoxicity [35,36]. After Faridi et al [37], the strength of the GICs was raised for the encapsulated form when compared to the manually mixed form.…”
Section: Discussionmentioning
confidence: 99%